Possible actions of methionine on embryonic development and postnatal phenotype of calves produced after embryo transfer - Masroor Sagheer; Quinn A. Hoorn; Oscar A. Ojeda-Rojas; Jeremy Block; Abigail J. Sproull; Daniella Heredia; Camila J. Cuellar; Tatiane S. Maia; McKenzie LJ. Haimon; Mariângela Bueno Cordeiro Maldonado; João H. Bittar; Angela M. Gonella-Diaza; et al. (Theriogenology, 2026)

Deep diving behaviour in oceanic manta rays and its potential function - Calvin S. Beale; Ferawati Runtuboy; Abraham B. Sianipar; Angela J. E. Beer; Kadarusman; Mark V. Erdmann; Edy Setyawan; Lydia Green; Clinton A. J. Duffy; Samantha Andrzejaczek; Barbara A. Block; Kerstin Forsberg; et al. (Frontiers in Marine Science, 2025)
Deep dives are performed by a range of marine megafauna, yet their function remains poorly understood. Proposed functions include foraging, predator avoidance, and navigation, but limited fine-scale data have hindered rigorous testing of these hypotheses. Here, depth time-series data from eight recovered and 16 non-recovered satellite tags deployed on oceanic manta rays ( Mobula birostris ) in Indonesia, Peru, and New Zealand were examined to characterise extreme dives and identify their potential function. From a total of 46,945 dives, 79 extreme dives (>500 m) were recorded, 11 of which were documented from recovered tags and associated high sampling frequency. Extreme dives were distinguished by rapid descents (up to 2.9 m s⁻¹), brief horizontal “steps” at depth, gradually slowing ascents, and extended periods spent near the surface both before and after diving. Unlike typical foraging dives, no substantial bottom phase was observed, and vertical oscillations—expected if feeding at depth—were absent. Extreme dives also occurred more frequently with increasing distance from the continental shelf edge as well as preceding periods of high 72h distance travelled, indicating they may inform subsequent movements. We propose that extreme dives enable oceanic manta rays to survey the properties of the water column, likely gathering environmental cues—such as temperature, dissolved oxygen, or geomagnetic gradients—to guide navigation and/or the decision to leave or remain in a general area. In open-ocean environments where external reference points are absent, such costly but infrequent dives may provide critical information for long-distance movements. Our results offer new insights into the role of extreme diving behaviour in oceanic manta rays and highlight the importance of fine-scale data for understanding deep-diving behaviours in marine megafauna.

Functional assessments of short-term spatial memory in the Dog Aging Project identify strong associations with age that are not moderated by body mass - Stephanie H. Hargrave; Amber J. Keyser; Emma Kristal; Gene E. Alexander; Theadora A. Block; Emily E. Bray; Laura E. L. C. Douglas; Brenda S. Kennedy; Daniel E. L. Promislow; David A. Raichlen; Dog Aging Project Consortium; Evan L. MacLean (GeroScience, 2025)

Prediction of assistance dog training outcomes using machine learning and deep learning models - Mohammad Hossein Amirhosseini; James A. Serpell; Emily E. Bray; Theadora A. Block; Laura E.L.C. Douglas; Brenda S. Kennedy; Katy M. Evans; Kathleen Freeberg; Piya Pettigrew (Applied Animal Behaviour Science, 2025)

Lunar cycle effects on pelagic predators and fisheries: insights into tuna, billfish, sharks, and rays - Samantha Andrzejaczek; Alexandra E. DiGiacomo; Chloe S. Mikles; Camille M. L. S. Pagniello; Theodore E. J. Reimer; Barbara A. Block (Reviews in Fish Biology and Fisheries, 2025)

A case study into the safety management systems for the effects of potential space weather risks, for operators of very high altitude ‘near space’ flights from Mojave Air & Space Port, California, and the associated regulatory challenges - C.T. Rees; J.R. Catchpole; A. Sewell; T. Reid; K.A. Ryden; S. Block; A. Mack (Journal of Space Safety Engineering, 2024)

Developing a range-wide sampling framework for endangered species: a case study with light-footed Ridgway’s rail - Bryan S. Stevens; Courtney J. Conway; Kimberly A. Sawyer; Lauren Kershek; Giselle Block; Sandra Hamilton; Rebecca Kolstrom (Biodiversity and Conservation, 2024)
Monitoring provides the foundation for evaluating recovery of endangered species, yet many species lack monitoring programs designed to integrate a species’ unique attributes, specific monitoring objectives, and principles of statistical sampling theory. We developed a framework for monitoring and assessment of endangered light-footed Ridgway’s rails ( Rallus obsoletus levipes ) across their U.S. range, relative to multi-scale recovery goals. We created spatially explicit sample units and a sampling frame covering all potential habitat to facilitate range-wide probability sampling, and also built a model of the call-broadcast process commonly used to survey marsh birds that included heterogeneity in availability for detection and conditional detectability for each bird during each survey. We used the model to simulate 96 sampling strategies that included different levels of replication, multiple approaches for sample allocation amongst strata, and both simple random and weighted probability sampling (i.e., weights proportional to local rail abundance) of sample units within strata. Effective monitoring surveyed ≥ 20–30% of the sampling frame on ≥ 3 occasions, with weighted sample selection and more targeted sampling (50% of units) for strata that are key to species recovery. We also tested Bayesian N-mixture models for estimating abundance and show that multiple models provide reasonable estimates. This work lays the foundation for statistical sampling and multi-scale population estimation for an endangered bird, and for refinement of abundance estimation models. Moreover, this work provides a replicable process for building customized and statistically defensible sampling frameworks to assess recovery of endangered species that can be used for other sensitive species.

The high-resolution imaging science experiment (HiRISE) in the MRO extended science phases (2009–2023) - A.S. McEwen; S. Byrne; C. Hansen; I.J. Daubar; S. Sutton; C.M. Dundas; N. Bardabelias; N. Baugh; J. Bergstrom; R. Beyer; K.M. Block; V.J. Bray; et al. (Icarus, 2024)

Characterizing dog cognitive aging using spontaneous problem-solving measures: development of a battery of tests from the Dog Aging Project - Stephanie H. Hargrave; Emily E. Bray; Stephanie McGrath; Gene E. Alexander; Theadora A. Block; Naomi Chao; Martin Darvas; Laura E. L. C. Douglas; Janet Galante; Brenda S. Kennedy; Breonna Kusick; Julie A. Moreno; et al. (GeroScience, 2024)

Global habitat predictions to inform spatiotemporal fisheries management: Initial steps within the framework - Heather D. Bowlby; Jean-Noël Druon; Jon Lopez; Maria José Juan-Jordá; María Teresa Carreón-Zapiain; Frederic Vandeperre; Agostino Leone; Brittany Finucci; Philippe S. Sabarros; Barbara A. Block; Haritz Arrizabalaga; Pedro Afonso; et al. (Marine Policy, 2024)

Structural design and engineering of Striatus, an unreinforced 3D-concrete-printed masonry arch bridge - A. Dell'Endice; S. Bouten; T. Van Mele; P. Block (Engineering Structures, 2023)

Complement component C1q is an immunological rheostat that regulates Fc:Fc$$γ$$R interactions - Edward C. So; Hua Zhou; Ariana Greenwell; Erin E. Burch; Yaping Ji; Emmanuel Y. Mérigeon; Henrik S. Olsen; Søren M. Bentzen; David S. Block; Xiaoyu Zhang; Scott E. Strome (Immunogenetics, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Global-Scale Environmental Niche and Habitat of Blue Shark (Prionace glauca) by Size and Sex: A Pivotal Step to Improving Stock Management - Jean-Noël Druon; Steven Campana; Frederic Vandeperre; Fábio H. V. Hazin; Heather Bowlby; Rui Coelho; Nuno Queiroz; Fabrizio Serena; Francisco Abascal; Dimitrios Damalas; Michael Musyl; Jon Lopez; et al. (Frontiers in Marine Science, 2022)
Blue shark ( Prionace glauca ) is amongst the most abundant shark species in international trade, however this highly migratory species has little effective management and the need for spatio-temporal strategies increases, possibly involving the most vulnerable stage or sex classes. We combined 265,595 blue shark observations (capture or satellite tag) with environmental data to present the first global-scale analysis of species’ habitat preferences for five size and sex classes (small juveniles, large juvenile males and females, adult males and females). We leveraged the understanding of blue shark biotic environmental associations to develop two indicators of foraging location: productivity fronts in mesotrophic areas and mesopelagic micronekton in oligotrophic environments. Temperature (at surface and mixed layer depth plus 100 m) and sea surface height anomaly were used to exclude unsuitable abiotic environments. To capture the horizontal and vertical extent of thermal habitat for the blue shark, we defined the temperature niche relative to both sea surface temperature ( SST ) and the temperature 100 m below the mixed layer depth ( T mld+100 ). We show that the lifetime foraging niche incorporates highly diverse biotic and abiotic conditions: the blue shark tends to shift from mesotrophic and temperate surface waters during juvenile stages to more oligotrophic and warm surface waters for adults. However, low productivity limits all classes of blue shark habitat in the tropical western North Atlantic, and both low productivity and warm temperatures limit habitat in most of the equatorial Indian Ocean (except for the adult males) and tropical eastern Pacific. Large females tend to have greater habitat overlap with small juveniles than large males, more defined by temperature than productivity preferences. In particular, large juvenile females tend to extend their range into higher latitudes than large males, likely due to greater tolerance to relatively cold waters. Large juvenile and adult females also seem to avoid areas with intermediate SST (~21.7-24.0°C), resulting in separation from large males mostly in the tropical and temperate latitudes in the cold and warm seasons, respectively. The habitat requirements of sensitive size- and sex-specific stages to blue shark population dynamics are essential in management to improve conservation of this near-threatened species.

Heat shocks, maize yields, and child height in Tanzania - S. Block; B. Haile; L. You; D. Headey (Food Security, 2022)

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Ancillary data from animal-borne cameras as an ecological survey tool for marine communities - T. K. Chapple; D. Tickler; R. C. Roche; D. T. I. Bayley; A. C. Gleiss; P. E. Kanive; O. J. D. Jewell; S. J. Jorgensen; R. Schallert; A. B. Carlisle; J. Sannassy Pilly; S. Andrzejaczek; et al. (Marine Biology, 2021)
Underwater visual surveys represent an essential component of coastal marine research and play a crucial role in supporting the management of marine systems. However, logistical and financial considerations can limit the availability of survey data in some systems. While biologging camera tag devices are being attached to an increasing diversity of marine animals to collect behavioral information about the focal species, the ancillary imagery collected can also be used in analytical techniques developed for diver-based surveys. We illustrate this approach by extracting ancillary data from shark-borne camera tag deployments focused on the behavior of a White shark ( Carcharodon carcharias) off Gansbaai, South Africa, and a Grey Reef shark ( Carcharhinus amblyrhynchos) within the Chagos Archipelago. Within the giant kelp forest environment of Gansbaai we could determine the spatial density of kelp thali and underlying substrate composition. Within the coral reef environment, the animal-borne video allowed us to determine the approximate percent and type of benthic cover, as well as growth form and genus of corals down to the upper mesophotic zone. We also enumerated fish species-level abundance over reef flat and wall environments. We used established dive-survey methods to analyze video data and found the results to be broadly comparable in the two systems studied. Our work illustrates the broad applicability of ancillary animal-borne video data, which is analogous in type and quality to diver-based video data, for analysis in established marine community survey frameworks. As camera tags and associated biologging technologies continue to develop and are adapted to new environments, utilising these data could have wide-ranging applications and could maximise the overall cost–benefit ratio within biologging deployments.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

Manipulating badges of status only fools strangers - Alexis S. Chaine; Daizaburo Shizuka; Theadora A. Block; Lynn Zhang; Bruce E. Lyon (Ecology Letters, 2018)
Conflict is risky, but mechanisms that allow animals to assess dominance status without aggression can reduce such costs. Two different mechanisms of competitor assessment are expected to evolve in different contexts: badges of status are expected in larger, anonymous groups, whereas individual recognition is feasible in small, stable groups. However, both mechanisms may be important when social interactions occur both within and across stable social groups. We manipulated plumage in golden‐crowned sparrows ( Zonotrichia atricapilla ) and found that two known badges of status – gold and black head plumage patch sizes – independently affect dominance among strangers but manipulations had no effect on dominance among familiar flockmates. Moreover, familiar flockmates showed less aggression and increased foraging relative to strangers. Our study provides clear experimental evidence that social recognition affects badge function, and suggests that variation in social contexts maintains coexistence and context‐dependent use of these two dominance resolution mechanisms.

Ureaplasma parvum causes hyperammonemia in a pharmacologically immunocompromised murine model - X. Wang; K. E. Greenwood-Quaintance; M. J. Karau; D. R. Block; J. N. Mandrekar; S. A. Cunningham; J. M. Mallea; R. Patel (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A novel application of multi‐event modeling to estimate class segregation in a highly migratory oceanic vertebrate - T. K. Chapple; T. Chambert; P. E. Kanive; S. J. Jorgensen; J. J. Rotella; S. D. Anderson; A. B. Carlisle; B. A. Block (Ecology, 2016)
Spatial segregation of animals by class (i.e., maturity or sex) within a population due to differential rates of temporary emigration ( TE ) from study sites can be an important life history feature to consider in population assessment and management. However, such rates are poorly known; new quantitative approaches to address these knowledge gaps are needed. We present a novel application of multi‐event models that takes advantage of two sources of detections to differentiate temporary emigration from apparent absence to quantify class segregation within a study population of double‐marked (photo‐identified and tagged with coded acoustic transmitters) white sharks ( Carcharodon carcharias ) in central California. We use this model to test if sex‐specific patterns in TE result in disparate apparent capture probabilities ( p o ) between male and female white sharks, which can affect the observed sex ratio. The best‐supported model showed a contrasting pattern of Pr( TE ) from coastal aggregation sites between sexes (for males Pr[ TE ] = 0.015 [95% CI = 0.00, 0.31] and Pr[ TE ]= 0.57 [0.40, 0.72] for females), but not maturity classes. Additionally, by accounting for Pr( TE ) and imperfect detection, we were able to estimate class‐specific values of true capture probability ( p * ) for tagged and untagged sharks. The best‐supported model identified differences between maturity classes but no difference between sexes or tagging impacts (tagged mature sharks p * = 0.55 (0.46–0.63) and sub‐adult sharks p * = 0.36 (0.25, 0.50); and untagged mature sharks p * = 0.50 (0.39–0.61) and sub‐adults p * = 0.18 (0.10, 0.31). Estimated sex‐based differences in p o were linked to sex‐specific differences in Pr( TE ) but not in p * ; once the Pr( TE ) is accounted for, the p * between sexes was not different. These results indicate that the observed sex ratio is not a consequence of unequal detectability and sex‐specific values of Pr( TE ) are important drivers of the observed male‐dominated sex ratio. Our modeling approach reveals complex class‐specific patterns in Pr( TE ) and p * in a mark‐recapture data set, and highlights challenges for the population modeling and conservation of white sharks in central California. The model we develop here can be used to estimate rates of temporary emigration and class segregation when two detection methods are used.

Inter-Grade and Inter-Batch Variability of Sodium Alginate Used in Alginate-Based Matrix Tablets - Shao Fu; Ira S. Buckner; Lawrence H. Block (AAPS PharmSciTech, 2014)

Reconstructing transoceanic migration patterns of Pacific bluefin tuna using a chemical tracer toolbox - Daniel J. Madigan; Zofia Baumann; Aaron B. Carlisle; Danielle K. Hoen; Brian N. Popp; Heidi Dewar; Owyn E. Snodgrass; Barbara A. Block; Nicholas S. Fisher (Ecology, 2014)
Large pelagic predators play important roles in oceanic ecosystems, and may migrate vast distances to utilize resources in different marine ecoregions. Understanding movement patterns of migratory marine animals is critical for effective management, but often challenging, due to the cryptic habitat of pelagic migrators and the difficulty of assessing past movements. Chemical tracers can partially circumvent these challenges by reconstructing recent migration patterns. Pacific bluefin tuna ( Thunnus orientalis ; PBFT) inhabit the western and eastern Pacific Ocean, and are in steep decline due to overfishing. Understanding age‐specific eastward transpacific migration patterns can improve management practices, but these migratory dynamics remain largely unquantified. Here, we combine a Fukushima‐derived radiotracer ( 134 Cs) with bulk tissue and amino acid stable isotope analyses of PBFT to distinguish recent migrants from residents of the eastern Pacific Ocean. The proportion of recent migrants to residents decreased in older year classes, though the proportion of older PBFT that recently migrated across the Pacific was greater than previous estimates. This novel toolbox of biogeochemical tracers can be applied to any species that crosses the North Pacific Ocean.

Passive Transdermal Systems Whitepaper Incorporating Current Chemistry, Manufacturing and Controls (CMC) Development Principles - Glenn A. Van Buskirk; Daniel Arsulowicz; Prabir Basu; Lawrence Block; Bing Cai; Gary W. Cleary; Tapash Ghosh; Mario A. González; David Kanios; Margareth Marques; Patrick K. Noonan; Terrance Ocheltree; et al. (AAPS PharmSciTech, 2012)

Genetic variants in the folate pathway and risk of childhood acute lymphoblastic leukemia - Catherine Metayer; Ghislaine Scélo; Anand P. Chokkalingam; Lisa F. Barcellos; Melinda C. Aldrich; Jeffrey S. Chang; Neela Guha; Kevin Y. Urayama; Helen M. Hansen; Gladys Block; Vincent Kiley; John K. Wiencke; et al. (Cancer Causes & Control, 2011)

Latitudinal and voltinism compensation shape thermal reaction norms for growth rate - LISA N. S. SHAMA; MELINA CAMPERO‐PAZ; K. MATHIAS WEGNER; MARJAN DE BLOCK; ROBBY STOKS (Molecular Ecology, 2011)
Latitudinal variation in thermal reaction norms of key fitness traits may inform about the response of populations to climate warming, yet their adaptive nature and evolutionary potential are poorly known. We assessed the contribution of quantitative genetic, neutral genetic and environmental effects to thermal reaction norms of growth rate for populations of the damselfly Ischnura elegans . Among populations, reaction norms differed primarily in elevation, suggesting that time constraints associated with shorter growth seasons in univoltine, high‐latitude as well as multivoltine, low‐latitude populations selected for faster growth rates. Phenotypic divergence among populations is consistent with selection rather than drift as Q ST was greater than F ST in all cases. Q ST estimates increased with experimental temperature and were influenced by genotype by environment interactions. Substantial additive genetic variation for growth rate in all populations suggests that evolution of trait means in different environments is not constrained. Heritability of growth rates was higher at high temperature, driven by increased genetic rather than environmental variance. While environment‐specific nonadditive effects also may contribute to heritability differences among temperatures, maternal effects did not play a significant role (where these could be accounted for). Genotype by environment interactions strongly influenced the adaptive potential of populations, and our results suggest the potential for microevolution of thermal reaction norms in each of the studied populations. In summary, the observed latitudinal pattern in growth rates is adaptive and results from a combination of latitudinal and voltinism compensation. Combined with the evolutionary potential of thermal reaction norms, this may affect populations’ ability to respond to future climate warming.

Relevance of Rheological Properties of Sodium Alginate in Solution to Calcium Alginate Gel Properties - Shao Fu; Ankur Thacker; Diana M. Sperger; Riccardo L. Boni; Ira S. Buckner; Sachin Velankar; Eric J. Munson; Lawrence H. Block (AAPS PharmSciTech, 2011)

Galectin-3 is associated with prostasomes in human semen - Jennifer L. Jones; Sarika Saraswati; Ashley S. Block; Cheryl F. Lichti; Maha Mahadevan; Alan B. Diekman (Glycoconjugate Journal, 2010)

Habitat and behaviour of yellowfin tuna Thunnus albacares in the Gulf of Mexico determined using pop‐up satellite archival tags - K. C. Weng; M. J. W. Stokesbury; A. M. Boustany; A. C. Seitz; S. L. H. Teo; S. K. Miller; B. A. Block (Journal of Fish Biology, 2009)
This study presents the first data on movement, habitat use and behaviour for yellowfin tuna Thunnus albacares in the Atlantic Basin. Six individuals were tracked in the Gulf of Mexico using pop‐up satellite archival tags. Records up to 80 days in length were obtained, providing information on depth and temperature preferences as well as horizontal movements. Thunnus albacares in the Gulf of Mexico showed a strong preference for the mixed layer and thermocline, consistent with findings for this species in other ocean basins. Fish showed a diel pattern in depth distribution, remaining in surface and mixed layer waters at night and diving to deeper waters during the day. The vertical extent of T. albacares habitat appeared to be temperature limited, with fish generally avoiding waters that were >6° C cooler than surface waters. The vertical and thermal habitat usage of T. albacares differs from that of bigeye Thunnus obesus and bluefin Thunnus thynnus , Thunnus orientalis and Thunnus maccoyii tunas. These results are consistent with the results of earlier studies conducted on T. albacares in other oceans.

Striped marlin ( Tetrapturus audax ) movements and habitat utilization during a summer and autumn in the Southwest Pacific Ocean - TIM J. SIPPEL; PETER S. DAVIE; JOHN C. HOLDSWORTH; BARBARA A. BLOCK (Fisheries Oceanography, 2007)
Six striped marlin ( Tetrapturus audax ) were caught on hook and line from recreational fishing boats near northern New Zealand (34°S, 174°E) and tagged and released with pop‐off satellite archival tags. For periods ranging from 22 to 60 days over the geographical range 168°E–170°W and 13–34°S, five tags collected a total of 202 days (range of 21–60 days) of data. These data permit the investigation of striped marlin geographical and vertical movements and water temperatures occupied from February to June 2003. One hundred and one days of geoposition data showed a preliminary view of their movements in and around New Zealand waters. Transmitted temperature and depth data indicated striped marlin spent 80% (±2%) of their time in the mixed layer including 72% (±2%) of their time in the top 5 m. Temperature data indicated 75% (±10%) of the striped marlin’s time was spent in water temperatures between 20.1 and 24.0°C. Tagged striped marlin moved faster during periods of directed movement away from New Zealand versus periods of passive movements when the fish were proximal to New Zealand or not moving in any specific direction. These data support some existing hypotheses about striped marlin physiological ecology and allow preliminary suggestions about how striped marlin bycatch might be reduced.

High apex predator biomass on remote Pacific islands - Charlotte Stevenson; Laure S. Katz; Fiorenza Micheli; Barbara Block; Kimberly W. Heiman; Chris Perle; Kevin Weng; Robert Dunbar; Jan Witting (Coral Reefs, 2007)

Effects of Fipronil and Chlorpyrifos on Endocrine-Related Endpoints in Female Grass Shrimp (Palaemonetes pugio) - D. C. Volz; E. F. Wirth; M. H. Fulton; G. I. Scott; E. Strozier; D. S. Block; J. L. Ferry; S. S. Walse; G. T. Chandler (Bulletin of Environmental Contamination and Toxicology, 2003)

Biofilms in Drinking Water Distribution Systems - M. Batté; B.M.R. Appenzeller; D. Grandjean; S. Fass; V. Gauthier; F. Jorand; L. Mathieu; M. Boualam; S. Saby; J.C. Block (Reviews in Environmental Science and Bio/Technology, 2003)

Planetary habitability: is Earth commonplace in the Milky Way? - S. Franck; A. Block; W. Bloh; C. Bounama; I. Garrido; H.-J. Schellnhuber (The Science of Nature, 2001)

Gas and fluid venting at the Makran accretionary wedge off Pakistan - U. von Rad; U. Berner; G. Delisle; H. Doose-Rolinski; N. Fechner; P. Linke; A. Lückge; H. A. Roeser; R. Schmaljohann; M. Wiedicke; SONNE 122/130 Scientific Parties; M. Block; et al. (Geo-Marine Letters, 2000)

Thermal tolerance and acclimation response of larvae of the sub-Antarctic beetle Hydromedion sparsutum (Coleoptera: Perimylopidae) - J. S. Bale; W. Block; M. R. Worland (Polar Biology, 2000)

Renal handling of drugs in the healthy elderly - D. Fliser; I. Bischoff; A. Hanses; S. Block; M. Joest; E. Ritz; E. Mutschler (European Journal of Clinical Pharmacology, 1999)

Hydrology, water availability and tundra ecosystem function in a changing climate: the need for a closer integration of ideas? - I. D. Hodkinson; N. R. Webb; J. S. Bale; W. Block (Global Change Biology, 1999)
Hydrologists and ecologists studying tundra ecosystems have worked largely independently, with little cross‐fertilization between disciplines. Their disciplines are, however, inextricably linked by a need to understand the dynamics and significance of the common substance water, in its liquid, solid and gaseous state within tundra environments. The impacts of predicted long‐term changes in climate have particularly important consequences for the functioning of tundra systems and there is a pressing need to initiate studies that integrate hydrological and ecological methodologies and concepts. Our paper attempts to summarize existing information on the role of water within tundra ecosystems, to emphasize the fundamental links between the biotic and the physico/chemical environments and to suggest how a closer integration of ideas might be achieved. Given the breadth of the subject matter the paper is intended to be illustrative rather than comprehensive. The paper examines the physical impacts of water in its various states on the tundra environment, emphasizing in particular the causes of spatial variation in water availability to living organisms. The significance of water is discussed for a range of organism groups, including plants, invertebrates and microorganisms and its pivotal role in ecosystem function and disturbance stressed. The need to develop integrated hydological/ecological models for tundra systems on different spatial scales is emphasized.

Mexican Spotted Owl Home Range and Habitat Use in Pine-Oak Forest: Implications for Forest Management - Joseph L. Ganey; William M. Block; Jeffrey S. Jenness; Randolph A. Wilson (Forest Science, 1999)
To better understand the habitat relationships of the Mexican spotted owl (Strix occidentalis lucida), and how such relationships might influence forest management, we studied home-range and habitat use of radio-marked owls in ponderosa pine (Pinus ponderosa)-Gambel oak (Quercus gambelii) forest. Annual home-range size (95% adaptive-kernel estimate) averaged 895 ha ± + 70 (SE) for 12 individuals and 997 ha ± 186 (SE) for 7 pairs of owls. On average, the 75% adaptive-kernel contour (a probability contour containing 75% of the owl locations) included 32 and 30% of the annual home range for individuals and pairs, respectively, suggesting high concentration of activity in a relatively small portion of the home range. Relative area of three cover types (ponderosa pine forest, pine-oak forest, and meadow) did not differ between seasonal ranges, and owls used these cover types in proportion to their relative area during both breeding and nonbreeding seasons. In contrast, relative area of four canopy-cover classes varied between seasons. Breeding-season ranges contained greater proportions of areas with canopy cover ≥ 60% and lower proportions of areas with 20-39% canopy cover than nonbreeding-season ranges. Owls roosted and foraged in stands with ≥ 60% canopy cover more than expected during both breeding and nonbreeding seasons, and used stands with 20-39% canopy cover less than expected except for foraging during the breeding season. Stands used for foraging did not differ in structure between seasons and had greater canopy cover and less rock cover than stands with no documented use. Stands used for roosting differed between seasons in a multivariate comparison, but no individual habitat variables differed between seasons in subsequent univariate comparisons. In both seasons, stands used for roosting had greater canopy cover than stands with no roosting use. Closed-canopy forests, which were used heavily by owls, were relatively rare on the study area, suggesting that such forests warrant special protection in areas managed for spotted owls. This may conflict with efforts to restore more open conditions in ponderosa pine forests. For. Sci. 45(1):127-135.

Failure of Mass Antibiotic Prophylaxis to Control a Prolonged Outbreak of Meningococcal Disease in an Israeli Village - S. Shehab; N. Keller; A. Barkay; L. Leitner; A. Leventhal; C. Block (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Comparative nutritional ecology of grass-feeding in a sub-Antarctic beetle: the impact of introduced species on Hydromedion sparsutum from South Georgia - S. L. Chown; W. Block (Oecologia, 1997)

Lack of correspondence between virus-induced human leukocyte interferon and concanavalin A-induced human migration inhibitory factor (MIF) - L. -H. Block; K. Cantell; S. Bamberger; G. Ruhenstroth-Bauer; H. Strander (Archives of Virology, 1978)